2019
DOI: 10.1530/jme-18-0237
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and miRNAs in assessment of ovarian tissue damage following cryopreservation

Abstract: Ovarian cortical tissue cryopreservation is a relatively novel approach to preserving fertility in women diagnosed with cancer. However, the effects of freezing-thawing are not fully understood, mainly due to the lack of suitable methods to assess tissue’s survival after thawing. Disparities in steroid production have been associated with ovarian failure by disrupting folliculogenesis, ovulation and oocyte apoptosis. Moreover, specific miRNAs, identified in human ovarian follicles, are thought to play a fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Many studies have been conducted to search for cancer biomarkers using mRNA from cryopreserved ovarian tissue or section staining of the tissue with antibodies [ 16 , 18 , 34 , 35 ]. Different research groups have started conducting studies to search for circulating miRNAs [ 36 , 37 ] or miRNAs in the tissue [ 20 , 38 , 39 , 40 ] as specific cancer biomarkers, but a study of miRNA expression after cryopreservation has just been recently published [ 19 ]. This study showed that upregulated miRNA–24 and downregulated expression of miRNA–193b, miRNA–320A, and steroid production could be non-invasive (expression patterns in culture media) markers for cell damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted to search for cancer biomarkers using mRNA from cryopreserved ovarian tissue or section staining of the tissue with antibodies [ 16 , 18 , 34 , 35 ]. Different research groups have started conducting studies to search for circulating miRNAs [ 36 , 37 ] or miRNAs in the tissue [ 20 , 38 , 39 , 40 ] as specific cancer biomarkers, but a study of miRNA expression after cryopreservation has just been recently published [ 19 ]. This study showed that upregulated miRNA–24 and downregulated expression of miRNA–193b, miRNA–320A, and steroid production could be non-invasive (expression patterns in culture media) markers for cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…These practices include histological and immunohistochemical evaluations for: (1) structural, functional, and DNA integrity; (2) malignant cell contamination; and polymerase chain reaction (PCR) for the detection of molecular tumor markers [ 16 , 17 , 18 ]. Moreover, currently, disparities in steroid production and altered expression of specific microRNAs (miRNAs), e.g., miRNA–193b, miRNA–320A, and miRNA–24, after cryopreservation have been associated with failure of ovarian tissue functioning and folliculogenesis [ 19 ]. MicroRNAs are a class of small non–coding RNA molecules that have been shown to be potential biomarkers for different cancers and prognostics [ 20 ] and are involved in gametogenesis, embryo development, and fertility [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic defects in BRCA1/2 [ 224 , 225 ], minichromosome maintenance complex component 8/9 [ 226 ], helicase for meiosis 1 [ 227 ], nucleoporin 107 [ 228 ], and synaptonemal complex central element protein 1 [ 229 ] are suggested to be implicated in ovarian insufficiency. Disparities in steroid production and altered expression of specific microRNAs (miRNAs), e.g., miRNA–193b, miRNA–320A, and miRNA–24, after cryopreservation are also related to impaired ovarian functioning and folliculogenesis [ 230 ]. For OTC, recent advances allow examination of tissue vitality; structural, functional, and DNA integrity; malignant cell contamination; and detection of molecular tumor markers [ 231 ].…”
Section: Future Perspectives Of Fpmentioning
confidence: 99%